Adaptive technologies and business integration social, managerial, and organizational dimensions - Cruz-Cunha, Maria Manuela, 1964-; Cortes, Bruno Conceicao, 1976-; Putnik, Goran, 1954- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
Adaptive Technologies and Business Integration: Social, Managerial and Organizational Dimensions provides an authoritative review of both intra-organizational and inter-organizational aspects in business integration, including: managerial and organizational integration, social integration, and technology integration, along with the resources to accomplish this competitive advantage. This premier reference source contains the most comprehensive knowledge on business integration. It provides an all-encompassing perspective on the importance of business integration in the emerging networked, extended, and collaborative organizational models.